Local dynamic range compensation for scanning electron microscope imaging system by sub‐blocking multiple peak HE with convolution. Issue 6 (30th November 2015) - Sim, K. S.; Teh, V.; Tey, Y. C.; Kho, T. K.
Summary: This paper introduces new development technique to improve the Scanning Electron Microscope (SEM) image quality and we name it as sub‐blocking multiple peak histogram equalization (SUB‐B‐MPHE) with convolution operator. By using this new proposed technique, it shows that the new modified MPHE performs better than original MPHE. In addition, the sub‐blocking method consists of convolution operator which can help to remove the blocking effect for SEM images after applying this new developed technique. Hence, by using the convolution operator, it effectively removes the blocking effect by properly distributing the suitable pixel value for the whole image. Overall, the SUB‐B‐MPHE with convolution outperforms the rest of methods. SCANNING 38:492–501, 2016. © 2015 Wiley Periodicals, Inc.